Social security payments and financialization: Lessons from the Greek case - Dionysios Kyriakopoulos; John Yfantopoulos; Theodoros V. Stamatopoulos (Journal of Risk and Financial Management, 2022)
This paper is founded on both the theoretical schemes of financialization, as a new regime of accumulation, and the shareholder value, the everyday finance, the structured finance, as well as the finance-led growth regime, whose special institutional forms concern the wage-labor nexus, the competition form, the monetary regime, the state-society relations, the insertion into the international regime, and the coherence and dynamic of the growth regime. It also aims to examine if the Greek social security system (the "system") used financial logic in economic policy during the period of 2000q1-2021q3. It is econometrically approached through the short-run Granger causality tests but mainly the autoregressive distributed lag model in order to estimate the long-run relationships of the social contributions and benefits paid, with variables expressing the financialization either of the whole economy or particularly of one of the public sectors. So, these steady-state relationships proved statistically significant, and they are considered to be compatible with several mechanisms of the finance-led growth regime. Thus, the sustainability of the "system" should be insured by the policy makers in the economic progress and the creation of new jobs able to fund it. This article contributes to the literature by offering empirical evidence on the financialization and relevant compilation analysis.
Keywords: 650; Granger causality; ARDL; Greek economy; finance-led growth regime; financialization paradigm; social security system